2020
DOI: 10.3390/biom10010112
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insight into Stereoselective ADME Characteristics of C20-24 Epimeric Epoxides of Protopanaxadiol by Docking Analysis

Abstract: Chirality is a common phenomenon, and it is meaningful to explore interactions between stereoselective bio-macromolecules and chiral small molecules with preclinical and clinical significance. Protopanaxadiol-type ginsenosides are main effective ingredients in ginseng and are prone to biotransformation into a pair of ocotillol C20-24 epoxide epimers, namely, (20S,24S)-epoxy-dammarane-3,12,25-triol (24S-PDQ) and (20S,24R)-epoxy dammarane-3,12,25-triol (24R-PDQ) that display stereoselective fate in vivo. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Theoretically, the understanding of molecular mechanisms involved in ligand-protein interactions is crucial for drug design. Guo et al investigated the chirality of C20-24 epimeric epoxides that transformed from protopanaxadiol-type ginsenosides [12]. Through the analysis of molecular docking, the authors confirmed consistency in some previous cell/animal-based experimental findings and gain insights into the stereo-selectivity of ginsenosides.…”
Section: Bioactivitiesmentioning
confidence: 66%
“…Theoretically, the understanding of molecular mechanisms involved in ligand-protein interactions is crucial for drug design. Guo et al investigated the chirality of C20-24 epimeric epoxides that transformed from protopanaxadiol-type ginsenosides [12]. Through the analysis of molecular docking, the authors confirmed consistency in some previous cell/animal-based experimental findings and gain insights into the stereo-selectivity of ginsenosides.…”
Section: Bioactivitiesmentioning
confidence: 66%